Legal Protection for Consumers in Trading Transactions Through the Tiktok Marketplace - Yogatama, Marga; Chairiyah, Muti Amanda; Sucipto, Adi (Generasi Sains Indonesia, 2026)
This study examines the effectiveness of consumer protection in transactions conducted through TikTok Marketplace as an emerging form of social commerce that integrates entertainment, algorithmic curation, and e-commerce features. Using a quantitative approach, data were collected from 150 respondents with purchasing experience on the platform and analyzed through descriptive statistics and multiple linear regression. The study focuses on four dimensions: consumer protection, transparency, allocation of responsibility, and dispute resolution mechanisms. The findings indicate that consumer protection is perceived at a moderate level, suggesting that existing legal frameworks are not fully effective in addressing the structural characteristics of social commerce. Transparency is identified as the most influential factor, followed by responsibility and dispute resolution. However, information is often embedded in persuasive and entertainment-driven formats, limiting clarity and informed decision-making. The study also reveals ambiguity in responsibility among platforms, sellers, and influencers, as well as limited confidence in platform-based dispute resolution systems. These results highlight the need for more adaptive regulatory approaches that integrate legal, technological, and behavioral dimensions to ensure effective consumer protection in digital marketplace environments.